Transitivity Analysis of CNN News Titles on the Israel-Palestine Ceasefire: Systemic Functional Linguistic Approach - Raisa Tanjia Ayesha Noori; zulprianto; Sawirman (EDU-KATA, 2026)
Language choices in news titles are never neutral. They systematically construct how readers understand who acts and who is affected. This study examines the transitivity structure in CNN news titles on the Israel-Palestine conflict following the ceasefire announced on January 19, 2025, using Systemic Functional Linguistics (SFL) as its theoretical framework. Data consist of 322 titles (669 clauses) published between January 19 and July 24, 2025, collected from CNN’s Middle East section via the Internet Archive and annotated using UAM Corpus Tool 6. The analysis identifies the distribution of Process types, Participant functions, and Circumstantial elements across the corpus. Results show that Material Processes dominate CNN’s titles construction (62.93%), followed by Verbal Processes (20.48%). In terms of Participant functions, Actor (30.93%) and Goal (27.79%) are the most frequent, yet CNN consistently employs ambiguous pronouns (‘it’, ‘they’) and passive constructions without explicit agents, reducing the identifiability of causal actors. Verbal processes frequently position Western and Israeli officials as primary Sayers, reflecting an editorial tendency toward diplomatic and institutional framing. Circumstantial elements are limited, with Location dominant (70.76%). These patterns indicate that CNN frames the conflict through procedural language in which events are reported without consistently traceable agents or explicit causal context.